Managerial development model of head of SMA in Padangsidempuan to achieve quality school - Siagian, Dunia; Rukun, Kasuk; Marsidin, Sufyarma; Anwar, Syafri (Journal of Educational Sciences, 2018)
The aim of this study is to develop a model of leadershipmanagerial competence of head of High School in Padangsidimpuan. Theexpected model can be used as a reference for school supervisors inconducting guidance of managerial competence of head of SMAPadangsidimpuan. This research was done using research and development(R and D) by applying the procedural model. The data of this research areconsisted of (1) qualitative data that was obtained from observation,interview, and documentation of the study and it was analyzed usingdescriptive statistics. (2) quantitative data by using questionnaire. Thequalitative data were analyzed using three ways, ie data reduction, datapresentation, and taking conclusions. The findings of this study are (1) Thecoaching is focused on the administrative aspect and has not yet touched themanagerial competence of the principal of SMA Padangsidimpuan and (2)the coaching process has not been done properly. This research resulted amodel of managerial competence development for the head of SMAPadangsidimpuan consisting of two components, namely (1) theidentification instrument of managerial competence and, (2) the steps ofcoaching the managerial competence of the principal of SMAPadangsidimpuan. This model is equipped with a support system thatincludes a program of leadership managerial competence of senior highschool Padangsidimpuan. The test results show that this model is practicaland effective for use in improving the managerial competence of SMAPadangsidimpuan. How well the model of guiding the managerialcompetence of the principal produced will not mean anything if its use doesnot get support from the parties related to the principal guidance inparticular and general education management. It is therefore necessary tosupport the school superintendent to use this model within thePadangsidimpuan.